Cover Image, Volume 88, Issue 4. (14th March 2018) - Gild, Matti L.; Topliss, Duncan J.; Learoyd, Diana; Parnis, Francis; Tie, Jeanne; Hughes, Brett; Walsh, John P.; McLeod, Donald S.A.; Clifton‐Bligh, Roderick J.; Robinson, Bruce G.
Abstract : The cover image, by Matti L. Gild et al., is based on the Unsolicited Review Clinical guidance for radioiodine refractory differentiated thyroid cancer, DOI:10.1111/cen.13508 .